Assessing the root development and biomass allocation of Magnolia champaca under various mulching at montane rainforest Cameron Highlands, Pahang, Malaysia - Rahmani, Wahidullah; Azizi, Frahnaz; Alias, Mohamad Azani (Korea Institute of Science and Technology Information, 2023)
The successful restoration program requires a comprehensive understanding of variables influencing seedling efficiency. Below-ground is hypothesized to have a major impact on seedling performance of species when planted in agriculture, and degraded areas with different types of mulching. This study investigated on Sg. Terla Forest Reserve in Cameron Highlands Pahang, Malaysia. In this study randomized complete block design (RCBD) was used. The excavation method was applied to study the root system development, above, and below ground biomass distributions under different types of mulching: coconut mulching (CM), oil palm mulching (OM), plastic mulching (PM) and control (CK). The root diameter, main root length, lateral root length, root coiling, and root direction toward to sun were recorded. The results in this study indicate that mulching had significant effect on root diameter, main root length, and root distributions among treatments while for lateral root length, root: shoot ratio, dry biomass distributions, and above and below ground biomass did not showed significant effect among treatments. The highest values for root diameter, lateral root length, main root length, root distributions, dry biomass distributions and above and below ground biomass were showed in CM treatments. However 75 of root coiling was observed in seedlings between treatments.